Total Plate Count and pH of Layer Eggs Immersed in Leaf Aqueous Extract of Averrhoa bilimbi L. - Suharyanto, Suharyanto; Marheny, Titik; Kususiyah, Kususiyah; Soetrisno, Edi; Hajrawati, Hajrawati (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2023)
Layer eggs are low cost and highly nutritious, but they are perishable. Therefore, it is important applying preservation for prolong its shelf life. Preservation by using natural agent such as belimbing wuluh (Averrhoa bilimbi L) leaf (BWL) extract for food safety and consumer health is ratioable. This study aimed to evaluate the immersion of layer eggs in an aqueous extract of BWL on the pH value and total microbial eggs. The treatments employed were eggs without soaking (P0), eggs soaked in aquadest (P1), eggs soaked in solution of BWL leaf extract (SBWLE) 15% (P2), eggs soaked in SBWLE 30% (P3), and eggs soaked in SBWLE 45% (P4). Soaking was carried out for 24 hours with the proportion of egg: water SBWLE was 1:13. The extraction process was carried out by boiling the BWL for 10 minutes at a temperature of 85 ºC. The boiled water is filtered and the results were used for treatment. The data were analyzed by ANOVA and he significant effect (P <0.05) of treatments were tested by a post hoc Duncan's Multiple Range Test (DMRT). The results showed that eggs soaked in SBWLE had lower pH and total microbes than eggs without soaking and eggs soaked in aquadest. The higher concentration of SBWLE, the decreasing pH and total microbes in eggs. The conclusion was that the use of SBWLE 15-45% (w/v) was able to suppress egg microbial growth and prevent an increase in egg pH. Keywords: Averhoa bilimbi, egg quality, microbes, pH